The Relationship of Vitamin D Topolycystic Ovary Syndrome (PCOS) Teenagers at Koto Tangah Padang District High School in 2022 - Utomo, Hardi Cahyo; Yuad, Haviz; Burhan, Ida Rahmah (Fakultas Kedokteran Universitas Andalas, 2024)
PCOS is characterized by increased ovarian and adrenal androgen secretion, hyperandrogenic symptoms such as hirsutism, acne and/or alopecia, menstrual irregularities, and polycystic ovaries. The prevalence of PCOS in 2016 was 6−21% of reproductive age worldwide. PCOS is the most common female endocrine disorder with a prevalence of around 4-6% in women of reproductive age in Indonesia. Vitamin D deficiency can increase PCOS symptoms. The research design was cross-sectional. The study was conducted at SMA N 7, SMA N 8 and SMA N 13 Padang in Koto Tangah District in May-August 2022. The research sample was high school students who experienced menstrual cycle disorders and were willing to agree to informed consent for the study with a sample size of 59 respondents. Vitamin D levels were examined using the 25-Hydroxyvitamin D ELISA Kit. Data were analyzed by chi-square test. The results showed that 86.4% of respondents experienced vitamin D deficiency. Statistically there was a relationship between PCOS in adolescents accompanied by hyperandrogens and vitamin D levels, there was a relationship between PCOS in adolescents accompanied by obesity and vitamin D levels, there was no relationship between PCOS in adolescents accompanied by acanthosis nigrican and vitamin D levels, and there was no relationship between PCOS in adolescents accompanied by hyperandrogens, obesity and acanthosis nigrican with vitamin D levels in SMA Koto Tangah District Padang in 2022. The conclusion of this study is that there is a relationship between PCOS in adolescents accompanied by hyperandrogens and vitamin D levels and there is a relationship between PCOS in adolescents accompanied by obesity and vitamin D levels.